Sulam Project: Tuberculosis (TB) Health Education for Primary School Students as a community service collaboration between the Department of Biology FMIPA UNP and UPSI Malaysia - Yosi Laila Rahmi; Elsa Yuniarti; Helsa Rahmatika; Dwi Hilda Putri; Heffi Alberida; Syakirah binti Samsudin (Pelita Eksakta, 2023)
Tuberculosis (TB) is a global issue that is a priority in both Indonesia and Malaysia. Since being designated by WHO at 1993 as a global public health threat, Tuberculosis (TB) has become one of the top 10 leading causes of death worldwide. Recently, the number of Tuberculosis (TB) patients in Indonesia has increased, especially paediatric TB cases. In addition, Tuberculosis (TB) cases also increased in Malaysia. For the West Sumatra region, the highest number of TB patients is in Padang City. Since Tuberculosis (TB) is a disease that can affect anyone including children, the school environment as one of the places where children gather and interact has the opportunity to be a place for the spread of TB cases as well as having an important role in preventing TB transmission. However, in reality, the role of schools in early prevention efforts related to Tuberculosis (TB) disease in children, especially elementary school students, is still not optimal. In line with this, Tuberculosis (TB) disease is closely related to the human respiratory system which is one of the topics discussed in the human anatomy and physiology course in the MBKM activity between the Department of Biology FMIPA UNP and the Department of Biology UPSI. Therefore, it is necessary to make preventive efforts in the form of Tuberculosis prevention education. The results of community service are that several stages of community service activities have been carried out regarding Tuberculosis (TB) prevention education for elementary school students, namely the students involved are enthusiastic about the activities held, then pre-service biology teacher are also actively engaged in preparing and carrying out this activity and students' knowledge related to general knowledge, symptoms, their relationship with the respiratory system and prevention efforts are classified as good.